Organizational Culture Assessment Instrument (OCAI): An Analysis of Organizational Culture Mapping at PT BBB Bandung - Putri, Novita Delima; Wahyuni, Siti; Zeinora; Herawati, Mirna; Hapsari, Fadjriah; Putradavi, Muhammad Farhans (Formosa Journal of Sustainable Research, 2024)
Organizational Culture Assessment Instrument (OCAI) consists of six dimensions that describe organizational culture. Assessment of organizational culture is important to be the basis for future organizational development. This study uses non-causal-comparative research. The purpose of the study was to analyze organizational culture at PT BBB using OCAI (organization culture assessment instrument). The results of the study showed that Adhocracy culture and Clan culture were shown from a total presentation of 26% for Adhocracy culture and 26% for Clan culture. This shows that currently there is a sense of commitment to creating innovation and development, dynamic and entrepreneurial as well as commitment and concern for members. This is not much different from what is expected by all employees for the perception of culture that is expected for the future